Development of digitalization mechanism of institute of financial ombudsman on example of Ukraine - Pozniakova, Olena; Dobosh, Nazar (Technology audit and production reserves, 2020)
The object of research is the problem of the rights violation of consumers of financial services. The institute of financial ombudsman is important for this function. This is the person who successfully performs the function of settling disputes in many countries around the world. The authors have developed a mechanism for digitalization of the institute of financial ombudsman, which will help in resolving disputes and preventing them through a special electronic platform of the financial ombudsman, which would optimize the cooperation of consumers of financial services with the ombudsman. This model of interaction with the mediator will be especially useful during a pandemic, COVID-19, in particular. Let’s believe that the process of appealing to the financial ombudsman through electronic systems for submitting and receiving the information will ensure the efficiency of service delivery, equal access to the procedure of consultation, and protection of all segments of the population. Analytical review of consumer protection violations was carried out based on statistical data of Ukraine, but the proposal to introduce a mechanism for the financial ombudsman digitalization is quite simple and universal for implementation in many countries. Statistics on complaints about violations in the provision of financial services in both the banking and non-banking financial sectors indicate the need to pay more attention to simplifying citizens' appeals to the regulator. The authors' survey of young people confirmed a low level of trust in banking and non-banking financial market institutions. It is important that the mediator actively participates not only in the stage of appealing disputes but also in preventing them in the form of dialogue with the consumer and the implementation of the rights and obligations of both parties. This will ensure a high level of financial inclusion, increase public confidence in the financial sector, as well as the level of financial literacy of the population.